Possible approach to complex liposomal drug delivery system design - D. A. Bezrukov; T. G. Balandin; S. M. Deyev; V. V. Popenko; A. P. Kaplun (Тонкие химические технологии)
Problems of complex liposomal targeted drug delivery systems with controlled release thermosensitive sterically stabilized active-loaded with doxorubicine and targeted with barstar liposomes producing